2021
DOI: 10.9778/cmajo.20200174
|View full text |Cite
|
Sign up to set email alerts
|

Adoption, feasibility and safety of a family medicine–led remote monitoring program for patients with COVID-19: a descriptive study

Abstract: Background: Virtual care for patients with coronavirus disease 2019 (COVID-19) allows providers to monitor COVID-19-positive patients with variable trajectories while reducing the risk of transmission to others and ensuring health care capacity in acute care facilities. The objective of this descriptive analysis was to assess the initial adoption, feasibility and safety of a family medicine–led remote monitoring program, COVIDCare@Home, to manage the care of patients with COVID-19 in the community… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“… 11 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The RPM models in eight studies did not include pulse oximetry as a monitoring tool for all participants but only for specific subgroups, and these studies were excluded. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 One study was excluded owing to reporting irrelevant outcomes, focusing on therapeutic options with less emphasis on the RPM model. 43
Figure 2 PRISMA diagram showing the study selection process
…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The RPM models in eight studies did not include pulse oximetry as a monitoring tool for all participants but only for specific subgroups, and these studies were excluded. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 One study was excluded owing to reporting irrelevant outcomes, focusing on therapeutic options with less emphasis on the RPM model. 43
Figure 2 PRISMA diagram showing the study selection process
…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive leadership and ongoing improvement cycles were used to adapt the program to meet system needs as the pandemic evolved [ 29 ]. An in-depth description of the strategies used to adapt the program and additional contextual factors are provided elsewhere [ 29 ], as are details about the model of care [ 27 ]. A patient-facing outline of the program is provided in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to conduct a comprehensive evaluation of the first 8 months of COVIDCare@Home (CC@H), a remote monitoring program, based at Women’s College Hospital (WCH) in Toronto, Canada, that aims to address the clinical and socioeconomic needs of patients during the acute phase of COVID-19. A detailed description of the program is provided separately [ 27 ]. Lessons from this program may be more broadly applicable to the use of remote monitoring for other acute and chronic conditions and are thus highly amenable to a primary care/family medicine approach [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported on the safety of similar programmes, but have lacked comparators. 8,[27][28][29][30]…”
Section: Comparison With Other Studiesmentioning
confidence: 99%